2015
DOI: 10.1371/journal.pone.0145095
|View full text |Cite
|
Sign up to set email alerts
|

Protumoral TSP50 Regulates Macrophage Activities and Polarization via Production of TNF-α and IL-1β, and Activation of the NF-κB Signaling Pathway

Abstract: Testes-specific protease 50 (TSP50) is abnormally overexpressed in many kinds of cancers and promotes cell proliferation and migration. However, whether TSP50 can influence the tumor microenvironment, especially the function of immune cells in the microenvironment, remains largely unknown. We demonstrated that exposure to the conditioned medium from TSP50-overexpressing cells, or co-culture with TSP50-overexpressing cells, enhanced the cytokine production and phagocytic activities of macrophages, and induced M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Wnt/ β -catenin and notch signaling are known to promote M2 macrophage polarization and signaling through IL-4 and IL-13 [2527]. Yang et al reported that the testes-specific protease 50 modulates macrophages and induces M2 polarization via TNF- α , IL-1 β , and NF- κ B signaling pathways [28]. Recently, the transcription factors MafB, Klf4, and Stat6 have been reported to promote M2 polarization by inducing the genes related to anti-inflammatory functions [2931].…”
Section: Discussionmentioning
confidence: 99%
“…Wnt/ β -catenin and notch signaling are known to promote M2 macrophage polarization and signaling through IL-4 and IL-13 [2527]. Yang et al reported that the testes-specific protease 50 modulates macrophages and induces M2 polarization via TNF- α , IL-1 β , and NF- κ B signaling pathways [28]. Recently, the transcription factors MafB, Klf4, and Stat6 have been reported to promote M2 polarization by inducing the genes related to anti-inflammatory functions [2931].…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA (3 μg) was reverse transcribed into cDNA according to instructions. The target genes were then amplified by RT-PCR or RT-qPCR with corresponding primers ( Table 1 ) as described previously [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…Whole cell extracts or cytosolic and nuclear extracts were prepared as previously described [ 32 , 33 ]. The extracts were then resolved by 12% sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE), transferred to a polyvinylidene fluoride (PVDF) membrane, and sequentially probed with various primary antibodies and horseradish peroxidase (HRP)-conjugated secondary antibodies for 1 h at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Total proteins and cytosolic-nuclear proteins were extracted as previously described [ 29 ]. The extracts were electro-blotted onto a polyvinylidene fluoride (PVDF) membrane following separation by 12% sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE).…”
Section: Methodsmentioning
confidence: 99%